Highly pathogenic avian influenza virus (H5N5) detected in an Atlantic walrus (Odobenus rosmarus rosmarus) in the Svalbard Archipelago, Norway, 2023 - Alexander Postel; Nele Gremmel; Christian Lydersen; Kit M. Kovacs; Luca A. Schick; Ursula Siebert; Ingebjørg H. Nymo; Paul Becher (Emerging Microbes and Infections)
We present the first documented case of highly pathogenic avian influenza virus (HPAIV) subtype H5N5 in an Atlantic walrus (Odobenus rosmarus rosmarus). The animal was found dead in Svalbard, Norway, in 2023. Sequence analysis revealed the highest genetic similarity with virus isolates from different avian hosts.